Has the acceptance of the equality and freedom principles increased over 15 years? A comparative analysis of attitudes among students - Czerniawska, Mirosława (Kultura-Społeczeństwo-Edukacja, 2020)
The publication deals with the description of attitudes towards the democratic principles of equality and freedom among students. The survey was conducted four times in five-year time intervals (2003, 2008, 2013, 2018). Samples had 325, 379, 368, and 371 respondents respectively. The author speculated that the advancement of the transformation is accompanied by growth of the acceptance of pro-democratic attitudes among students, namely the wider acceptance of the principles of equality and freedom. The attitudes were diagnosed using nine pairs of statements (these include both original statements and statements adopted from literature). The hypothesis was not confirmed. The acceptance of the principles of equality and freedom has not increased in consecutive surveys and for many statements the acceptance has decreased.